Versatile Nanocomposite Formulation System of Non-Steroidal Anti-Inflammatory Drugs of the Arylalkanoic Acids - Berber, Mohamed; Hafez, Inas; Minagawa, Keiji; Mori, Takeshi; Tanaka, Masami (IntechOpen, 2011)
None